J. M. Meech, Charter and Revised Ordinances of the City of Norwich With the Amendments Thereto, and Statutes of the State Relating to Municipal Corporations 178, 185 (1877) - (:unkn) unknown (My University, 1876)
Prohibited the discharge of any swivel, musket, fowling-piece, pistol, or other gun of any description within said city at a distance of less than "fifty rods" from any dwelling house, public highway, or street.Violators fined three dollars.
Keywords: DISCHARGE